METHODOLOGICAL ASPECTS OF PHOTODYNAMIC THERAPY OF EHRLICH SOLID CARCINOMA IN BALB/C MOUSE STRAIN WITH VARIOUS TUMOR LOCALIZATION - S. S. Kruglov; M. L. Gelfond; M. L. Tyndyk; M. A. Maydin; T. G. Grishacheva; R. M. Basina; E. A. Gubareva; E. A. Plakhov; G. S. Kireeva; A. V. Panchenko (Сибирский онкологический журнал)
Background. Photodynamic Therapy is one of the treatment methods used in modern oncology. Evaluation of the efficacy in vivo of photosensitizers on tumor models is generally accepted, but the photodynamic  therapy technique in mice is not without drawbacks.The purpose of the study was evaluation of the efficacy of photodynamic therapy in mice with Ehrlich tumor model after subcutaneous and intracutaneous injection of tumor cells.Material and Methods. The study was conducted on BAL B/C mice of both sexes. Fotoditazin® and Radachlorin® were used as photosensitizers. For photoactivation, the Alod laser apparatus with a wavelength of 662 nm was used.Results. A comparison of photodynamic therapy with subcutaneous and intracutaneous localization of Ehrlich tumor was performed. It was shown that depending on the location and depth of inoculation of Ehrlich tumor, the pharmacokinetics (both the fluorescence intensity over time and the contrast ratio of the tumor/surrounding tissue) and pharmacodynamics (tumor growth inhibition, survival) of photosensitizers are significantly different. Higher contrast of the tumor/surrounding tissue is observed with intracutaneous localization of the tumor.Conclusion. A model with intracutaneous localization of Ehrlich tumor can be recommended for a primary assessment of efficacy; it allows the use of fewer animals in the experiment. When planning experiments to study photosensitizers and evaluating their results, the advantages and disadvantages of different methods for modeling tumors in mice should be taken into account.